Successful Use of Intravenous B-blocker Therapy in Cardiogenic Shock Supported With Venoarterial Extracorporeal Membrane Oxygenation: A Case Series - Alaa Rahhal (14150403) (2022)
Tachycardia in cardiogenic shock (CS) might reduce the cardiac output (CO) by decreasing the ventricular filling time. Nevertheless, heart rate (HR) control with agents that possess negative inotropy might decrease the CO. Therefore, controlling the tachycardia in the setting of CS remains controversial. We herein describe four cases of patients presenting with myocardial infarction complicated with CS that required rescue venoarterial extracorporeal membrane oxygenation (VA-ECMO) initiation. Tachycardia was present with HR ∼130-140 beats per minute after VA-ECMO initiation, and hence esmolol was infused continuously at a starting dose of 10-20 mcg/kg/min and titrated according to HR. With the use of esmolol to control the HR in the setting of CS supported with VA-ECMO, lactate cleared, and echocardiographic parameters improved, allowing the four cases to be successfully decannulated from ECMO. Our report indicates that short-acting beta-blocker could be safely used in the complex scenario of severe tachycardia while supported with VA-ECMO. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2021.101071